SIGNIFICATION CONCEPTS IN GUDANG GARAM CIGARATTE ADVERTISEMENTS FROM THE 80s, 90s, and 2000s - Alam, Cempaka Maharani; Tujzahra, Raudya; Shindy, Regina Ayu Harna; Lestari, Tani Sintia (Universitas Gunadarma, 2019)
Advertising is one of the most effective and efficient tools since it combines audio and visual to display, describe, and demonstrate the advertised product in a short time. Gudang Garam television advertisements in 80s, 90s, 2000s are chosen to be analyzed since the three of which are considered to be the representatives of Gudang Garam cigarette advertisements in each decade. The aim of this research is to find out the signification concepts represented in Gudang Garam advertisements. Considering the nature of the source data, this research uses qualitative as method. The research employed semiotic approach and Stuart Hall’s Representation as tools of analysis. The results are the significations concept that is used in the the first advertisement aired in the 80s is the universality of Gudang Garam cigarette consumers. Meanwhile, in the second advertisement, the signification concept found is the masculinity of Gudang Garam consumers. However, the signification concept found in the third advertisement is the modernization image of Gudang Garam as a cigarette manufacturer.